Synthesis, Characterization and Imaging of Fluorescine Isothiocyanate Conjugated Magnetite Nanoparticles in MCF 7 Breast Cancer Cell Lines - Mohammad E Khosroshahi; Maral Asemani (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2017)
<span style="font-size:11.0pt;font-family: "Calibri","sans-serif";mso-ascii-theme-font:minor-latin;mso-fareast-font-family: Calibri;mso-fareast-theme-font:minor-latin;mso-hansi-theme-font:minor-latin; mso-bidi-font-family:Gautami;mso-bidi-theme-font:minor-bidi;mso-ansi-language: EN-US;mso-fareast-language:EN-US;mso-bidi-language:AR-SA" lang="EN-US">In this work we describe fabrication, characterization and possible application of FITC (<span style="font-size:11.0pt;font-family:"Calibri","sans-serif"; mso-ascii-theme-font:minor-latin;mso-fareast-font-family:Calibri;mso-fareast-theme-font: minor-latin;mso-hansi-theme-font:minor-latin;mso-bidi-font-family:Gautami; mso-bidi-theme-font:minor-bidi;mso-ansi-language:EN-GB;mso-fareast-language: EN-US;mso-bidi-language:AR-SA" lang="EN-GB">fluorescine isothiocyanate<span style="font-size:11.0pt;font-family:"Calibri","sans-serif"; mso-ascii-theme-font:minor-latin;mso-fareast-font-family:Calibri;mso-fareast-theme-font: minor-latin;mso-hansi-theme-font:minor-latin;mso-bidi-font-family:Gautami; mso-bidi-theme-font:minor-bidi;mso-ansi-language:EN-US;mso-fareast-language: EN-US;mso-bidi-language:AR-SA" lang="EN-US">) conjugated magnetite nanoparticles (MNPs) for biomedical applications such as imaging of cancer cells. The MNPs possessed octahedral-like geometry with almost completely dispersed distribution with high saturation magnetization. The final FMNPs (<span style="font-size:11.0pt;font-family:"Calibri","sans-serif";mso-ascii-theme-font: minor-latin;mso-fareast-font-family:Calibri;mso-fareast-theme-font:minor-latin; mso-hansi-theme-font:minor-latin;mso-bidi-font-family:Gautami;mso-bidi-theme-font: minor-bidi;mso-ansi-language:EN-GB;mso-fareast-language:EN-US;mso-bidi-language: AR-SA" lang="EN-GB">fluorescine isothiocyanate <span style="font-size: 11.0pt;font-family:"Calibri","sans-serif";mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri;mso-fareast-theme-font:minor-latin;mso-hansi-theme-font: minor-latin;mso-bidi-font-family:Gautami;mso-bidi-theme-font:minor-bidi; mso-ansi-language:EN-US;mso-fareast-language:EN-US;mso-bidi-language:AR-SA" lang="EN-US">magnetite nanoparticles) absorption band showed 30 nm red shift towards longer wavelength compared to bare MNP and the laser-induced fluorescence was observed at 518 nm. The MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide) results showed that FITC conjugation diminishes the toxicity MNPs mainly due to the reduction of surface charge. Fluorescence microscopy confirmed the uptake and distribution of FMNPs in MCF 7 (Michigan Cancer Foundation-7) breast cancer cells, which suggests that it can be utilized for applications such as a magnetic fluorescent probe for bioassay.